Nano BF3.SiO2 catalysed, microwave assisted Michaelis-Arbuzov reaction to synthesize biologically active phosphonates under solvent-free condition. (2018) - Ravikumar, D.; Subramanyam, Ch.; Mohan, S.; Chandra Sekhar, D.; Prasada Rao, K.
Abstract: Nano-BF3 .SiO2 is an efficient, reusable and eco-friendly catalyst for various organic reactions. So, this catalyst was applied for the synthesis of biologically active phosphonates via a microwave-mediated Michaelis-Arbuzov reaction. This approach is solvent free, high yielding, simple work-up process and short reaction time. The structure all the synthesized compounds was confirmed by spectral and CHN analysis. In vitro antibacterial and antifungal activity of these compounds was also analysed. Majority of the title compounds showed good inhibition towards bacteria and fungi.